EFFICACY OF ORMELOXIFENE IN MANAGEMENT OF DYSFUNCTIONAL UTERINE BLEEDING - Sawarkar, Umesh; Deshmukh, Sarang; Raut, Ashwini; Bhosale, Uma; Shenoyk, Ashok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective was to evaluate the efficacy of ormeloxifene in dysfunctional uterine bleeding (DUB) with respect to bleeding pattern and improvement in hemoglobin (Hb). Methods: This was an interventional study on 99 patients of DUB visiting the gynecology outpatient department over 1 year using semi-structured pro forma. After voluntary participation of patients, tablet ormeloxifene was given at the dose of 30 mg biweekly for 2 months. In case of a therapeutic response as informed by the patient, the dose was reduced to 30 mg weekly for a further period of 4 months. All patients were treated for 6 months. Type, amount, and duration of bleeding, frequency of menstrual cycle, passage of clots, and impact on Hb were assessed. Result and Observations: Menorrhagia was the main type of bleeding. 36–40 years of age group was the most common. After the intervention, 76.8% of women achieved a duration of bleeding of 4–5 days, and in 87% of women, menstrual cycle became regular. Passage of clots was reduced by 71.83%. Mean Hb concentration of study participants increased by 0.5 g/dl at the end of the study. Conclusion: Ormeloxifene is effective alternative and appears to be a promising option for the medical management of DUB.